The Impact of Fiscal Consolidation and Structural Reformson Growth in Japan - Berkmen, Pelin (Washington, D.C. : International Monetary Fund, 2011)
With Japan's public debt reaching historical levels, the need for fiscal consolidation and structural reforms have increased. As fiscal consolidation will require a sustained and large adjustment in the fiscal balance, its growth effect is a concern particularly for the short run. This paper uses the IMF's Global Integrated Monetary and Fiscal Model to analyze the growth impact of fiscal consolidation and structural reforms. Although fiscal consolidation has short-term costs, the potential long-term benefits are considerable, and reforms that raise potential growth could support consolidation. Simulations show that the external environment also matters but domestic policies should be the priority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet